Rare Case: Tetra-Amelia Syndrome - Alifa, Dhara; Aziz, Muhammad Alamsyah; Ritonga, Mulyanusa Amarullah; Pribadi, Adhi (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Congenital abnormalities are anomalies that become a fear for a family, when a mother experiences pregnancy. Some abnormalities are temporary and can be corrected, while some are permanent and cannot be corrected, so screening at antenatal time is very important.Objective: To explain and analyze a rare case of Tetra-amelia syndrome and how to diagnose it.Case: A 32-year-old woman with a 32-week-old G3P0A2 pregnancy visited the maternal-fetal clinic. According to ultrasound data, a single fetus with a gestational age of 31-32 weeks and a fetal weight of 1837 grams is in breech presentation. Only the proximal components of the arm and leg are formed, leaving the radius bones, ulna, tibia, and fibula unformed. The femur has a length that corresponds to 16 weeks, while the humerus has a length that corresponds to 20 weeks. These findings also revealed a discrepancy in pregnancy age. A tetra-amelia abnormality was discovered at the end of the ultrasound scan. Caesarean section performed on August 6, 2021, at the age of 39 weeks, a baby girl has been born baby girl a baby girl weighing 2300 grams, a body length of 31 cm, with mild asphyxia.Conclusion: During antenatal care, ultrasound on the unidentified distal part of the entire extremity can detect Tetra-amelia syndrome.Kasus Langka: Sindrom Tetra-ameliaAbstrak Pendahuluan: Kelainan bawaan adalah anomali yang menjadi trauma bagi keluarga, ketika seorang ibu mengalami kehamilan. Beberapa kelainan bersifat sementara dan dapat diobati, sementara beberapa bersifat permanen dan tidak dapat diperbaiki sehingga skrining pada waktu antenatal sangat penting.Tujuan: Artikel ini untuk menjelaskan dan menganalisis kasus langka sindrom Tetra-amelia dan cara mendiagnosisnya.Kasus: Seorang wanita berusia 32 tahun dengan kehamilan G3P0A2 berusia 32 minggu mengunjungi klinik fetomaternal. Hasil pemeriksaan ultrasonografi menunjukan janin tunggal dengan usia kehamilan 31 - 32 minggu dan berat janin 1837 gram dalam letak sungsang. Hanya komponen proksimal lengan dan kaki yang terbentuk, sedangkan tulang jari-jari, ulna, tibia, dan fibula tidak terbentuk. Femur memiliki panjang yang sesuai dengan 16 minggu, sedangkan humerus memiliki panjang yang sesuai dengan 20 minggu. Kelainan tetra-amelia dapat dideteksi dengan pemindaian ultrasonografi. Pada tanggal 6 Agustus 2021 presentasi sungsang, dilakukan operasi caesar, lahir bayi perempuan pada usia 39 minggu, berat 2300 gram, panjang 31 cm, disertai asfiksia ringan.Kesimpulan: Pemeriksaan ultrasonografi pada perawatan antenatal dapat mendeteksi sindrom Tetra-amelia, bila bagian distal ekstremitas tidak teridentifikasi.Kata kunci:Sindrom Tetra-amelia, Ultrasonografi, Kelainan Kongenital